2015
DOI: 10.1186/s13023-015-0326-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of patisiran for familial amyloidotic polyneuropathy: a phase II multi-dose study

Abstract: BackgroundTransthyretin-mediated amyloidosis is an inherited, progressively debilitating disease caused by mutations in the transthyretin gene. This study evaluated the safety, tolerability, pharmacokinetics, and pharmacodynamics of multiple doses of patisiran (ALN-TTR02), a small interfering RNA encapsulated within lipid nanoparticles, in patients with transthyretin-mediated familial amyloid polyneuropathy (FAP).MethodsIn this phase II study, patients with FAP were administered 2 intravenous infusions of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
233
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 281 publications
(239 citation statements)
references
References 29 publications
5
233
0
1
Order By: Relevance
“…15 In contrast, subcutaneously administered revusiran is targeted to the liver by a simple carbohydrate ligand that enables receptor-mediated uptake by the ASGPR expressed on hepatocytes and does not require any pre-medication. The level of TTR knockdown observed with revusiran administration in this study is comparable with that reported for intravenous patisiran (0.3 mg/kg every 3 weeks 16 ) and greater than that reported for the antisense oligonucleotide (ASO) agent IONIS-TTR RX in healthy volunteers. 17,18 The most common TEAEs for revusiran were mild to moderate ISRs and the signs and symptoms associated with these reactions.…”
Section: Discussionsupporting
confidence: 70%
“…15 In contrast, subcutaneously administered revusiran is targeted to the liver by a simple carbohydrate ligand that enables receptor-mediated uptake by the ASGPR expressed on hepatocytes and does not require any pre-medication. The level of TTR knockdown observed with revusiran administration in this study is comparable with that reported for intravenous patisiran (0.3 mg/kg every 3 weeks 16 ) and greater than that reported for the antisense oligonucleotide (ASO) agent IONIS-TTR RX in healthy volunteers. 17,18 The most common TEAEs for revusiran were mild to moderate ISRs and the signs and symptoms associated with these reactions.…”
Section: Discussionsupporting
confidence: 70%
“…Compared with other lipid formulations from industry leaders like DLin-MC3-DMA or MC3 [heptatriaconta-6,9,28,31-tetraen-19-yl 4-(dimethylamino)butanoate], LUNAR is five times more efficient. MC3 is the ionizable lipid component of Patisiran, which is currently in clinical trials for treatment of transthyretin-mediated familial amyloid polyneuropathy (FAP) (13,14). Additionally, doses of up to 10 mg/kg did not cause any increase in circulating aspartate aminotransferase (AST) or alanine aminotransferase (ALT) levels (markers associated with acute liver toxicity), thus establishing the safety of this technology (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…47 Unfortunately, these delivery approaches result in limited distribution primarily to the liver and are associated with such intense proinflammatory reactions that prophylactic doses of steroids, histamine antagonists, and NSAIDS are required prior to each administration, and despite these pretreatments, serious infusion reactions are reported in 20% or more of treated patients. [48][49][50][51][52][53][54] However, as mentioned briefly above, a more effective solution to the in vivo delivery of siRNA molecules (at least for the delivery of siRNA to hepatocytes) has been has been the conjugation of double-stranded siRNA molecules (and ASOs) to GalNAc moieties resulting in the active uptake of these conjugates into hepatocytes via Asialoglycoprotein receptors. 43 However, to achieve effective stability and distribution of GalNAcconjugated siRNAs, substantial additional chemical modifications must be incorporated, and thus, most GalNAc-conjugated siRNAs in development contain 10 to 14 PS moieties, 11 to 14 2ʹ-methoxy and 10 to 14 2ʹ-fluoro (2ʹ-F)-modified nucleosides.…”
Section: Rna Therapeutics Based On Antisense Principlesmentioning
confidence: 99%
“…However, several siRNA inhibitors are also currently being evaluated in cancer clinical trials, and in all these trials the siRNA molecules have been formulated into various types of nanoparticles including lipid nanoparticles or liposomes. [47][48][49][50][51][52] Most of these remain at early stages of development, and the data are not yet mature enough to determine their clinical potential. However, evidence of siRNA-mediated target inhibition on systemic delivery for a human solid tumor (melanoma) has been demonstrated, first in a clinical trial with CALAA-01, an siRNA-targeting ribonuclease reductase subunit 2 that is complexed with a cyclodextrin polymer coated with polyethylene glycol and decorated with human transferrin protein on the surface of the particle.…”
Section: Therapeutic Advances With Rna-based Therapeutics In Oncologymentioning
confidence: 99%